"Stakkars pappa" – hva kan far-barn-relasjonen si oss om barnerollen? - Hanne Kiil (Barnboken: Tidskrift för Barnlitteraturforskning, 2012)
“Poor daddy”–child's perspective and iconotext in three award-winning picture books. The Western dichotomy between children and adults characterize our opinion both on children and childhood. In this understanding framework the children are seen as something totally different from adults. Can artistic children's literature modify this habitual thinking about such hierarchical levels? The three books to examine closer have all won awards from Ministry of Culture as the best Norwegian picture book that year. Both Svein Nyhus: Pappa [Daddy] (1998), Hans Sande and Gry Moursund: Arkimedes og brødskiva [Archimedes and the Sandwich] (2000) and Stein Erik Lunde and Øyvind Torseter: Eg kan ikkje sove no [I Can't Sleep Now] (2008) are first-person narratives where the main character is a child. In such picture books visual and verbal point of view rarely are the same. The illustrations usually observe the central character from a distance and then allow the reader not only to adopt the narrator's point of view. What kind of ambiguities in the complex relationship between text and images give signals to the readers–and to the understanding of the narrator's position and perspective? What can this perspective and the iconotext in the three books tell us about today's children's role?